THE PRESERVATION OF ANDIR DANCE IN THE DEVELOPMENT OF CULTURAL TOURISM IN TISTA TOURISM VILLAGE - Ni Putu Sri Sujeni Setiawati; I Made Sugata; I Gusti Ngurah Pertu Agung (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Tista Tourist Village in Tabanan Regency, Bali, is a cultural tourism destination rich in traditions and arts, one of which is the Andir Dance. This sacred dance holds significant spiritual value. Within the context of cultural tourism development, the Andir Dance faces a major challenge: how to preserve its sacredness while also utilizing it as a tourist attraction. This study aims to analyze the preservation strategies of the Andir Dance to support sustainable cultural tourism development in Tista Tourist Village. The research uses a qualitative descriptive approach, with data collection techniques involving in-depth interviews, observation, and documentation studies. The study focuses on understanding the reasons behind the community’s effort to preserve the Andir Dance, the challenges faced, and the strategies employed to maintain its existence within the realm of cultural tourism. The results indicate that the Andir Dance has significant potential as a unique cultural tourism attraction; however, the primary challenges include limited dancer regeneration, insufficient documentation, and the underdevelopment of the village’s tourism infrastructure. A SWOT analysis suggests that preservation strategies should combine strengthening the local artistic community, cultural digitization, and enhancing human resource capacity and village tourism management. Preservation efforts must also balance maintaining the sacred values of the dance while remaining open to the tourism market.